2020
DOI: 10.17268/sci.agropecu.2020.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome (SARS-CoV-2): A national public health emergency and its impact on food security in Peru

Abstract: On March 16, 2020, a policy of quarantine and social isolation initiated in Peru imposed by the declaration of National Public Health Emergency for Severe Acute Respiratory Syndrome (SARS-CoV-2), which is affecting everyone. The research aimed to collect information that anticipates the impacts on the quantity and the need to distribute food for food security. From a global point of view, fiscal, monetary, and macro-financial policies corresponding to approximately 7% of the National GDP. These efforts will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…To improve the interconnection between each stage of the FSC and between each RFSC, Bakalis et al (2020), García et al (2020), Siche (2020), Vaio et al (2020), Chitrakar et al (2021) suggest implementing automation. This includes the application of digital and intelligent systems such as the internet of things (IoT), artificial intelligence (AI), and information and communication technologies (ICT).…”
Section: Use Of New Technologiesmentioning
confidence: 99%
“…To improve the interconnection between each stage of the FSC and between each RFSC, Bakalis et al (2020), García et al (2020), Siche (2020), Vaio et al (2020), Chitrakar et al (2021) suggest implementing automation. This includes the application of digital and intelligent systems such as the internet of things (IoT), artificial intelligence (AI), and information and communication technologies (ICT).…”
Section: Use Of New Technologiesmentioning
confidence: 99%
“…The values for extreme droughts (minimum SVI, ≤ -1.95) exceed up to 2.16 times the classification limit value (UN-SPIDER, 2020), as in the case of the Ayacucho Region (-4.23), or 1.57 times as in the case of the Tumbes Region (-3.08) (Table 2; Figure 1); this showed that these places deserve special attention due to their low water availability. Recalling that, in addition to this problem, there are the impacts caused by SARS-CoV-2 on the Peruvian agricultural sector, in terms of quantity and the need to distribute food for food security (García et al, 2020).…”
Section: Regional Standardized Vegetation Index (Svi)mentioning
confidence: 99%
“…The agricultural sector is affected by increased water stress in Andean dryland crops, as well as by the delay in planting for November in the central and southern highlands of Peru (Fernández, 2020). The impacts caused by SARS-CoV-2 on the agricultural sector, affecting the agri-food chain, added to this problem (García et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as global food demand, scarce cereal stocks, and climate change are emerging challenges to be confronted for the stability of food systems at the national and global levels [1][2][3]. Likewise, hunger has increased in Latin America and the Caribbean [4] and threatened a massive resurgence amid the coronavirus/COVID-19 pandemic [5][6][7]. Peru has a commodity-based economy in which agriculture plays an essential role in the nation's development [8,9].…”
Section: Introductionmentioning
confidence: 99%